2021
DOI: 10.1002/adma.202103013
|View full text |Cite|
|
Sign up to set email alerts
|

Reporting Excellent Transverse Piezoelectric and Electro‐Optic Effects in Transparent Rhombohedral PMN‐PT Single Crystal by Engineered Domains

Abstract: Transparent ferroelectric crystals with high piezoelectricity are challenging to build because of their complex structure and disordered domains in rhombohedral relaxor ferroelectrics. There are eight domains along the <111> direction, which cause light scattering. In this study, perfect transparency is achieved along the [110] and [001] directions in [110]‐poled rhombohedral 0.72Pb(Mg1/3Nb2/3)O3‐0.28PbTiO3 (PMN‐PT) crystals, which have a high d31 value of 1700 pC N−1 and a high electro‐optic coefficient γ33 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 51 publications
1
35
1
Order By: Relevance
“…This observation is consistent with that reported in another MPB-involved system Tb 1−x Dy x Fe 2 [ 39 ]. Interestingly, such a phenomenon was also observed recently in a ferroelectric MPB-involved system [ 40 ].…”
Section: Resultssupporting
confidence: 73%
“…This observation is consistent with that reported in another MPB-involved system Tb 1−x Dy x Fe 2 [ 39 ]. Interestingly, such a phenomenon was also observed recently in a ferroelectric MPB-involved system [ 40 ].…”
Section: Resultssupporting
confidence: 73%
“…Some other ferroelectric materials may also possess high EO coefficients ( r c > 200 pm V −1 ), such as (Sr,Ba)Nb 2 O 6 crystals ( 35 ), but these high values are a result of the ferroelectric phase transition temperature being close to room temperature, which greatly limits their operating temperature range. In addition, the EO coefficients of PIN-PMN-32PT crystals are much higher than that of previously reported relaxor ferroelectric crystals, including 011-poled PMN-28PT ( 21 ). This is due to the following two reasons: First, the composition of PIN-PMN-32PT is closer to the MPB when compared with the reported PMN-28PT.…”
Section: Transparency and Electro-optic Properties Of The 011-poled P...contrasting
confidence: 61%
“…The presence of naturally occurring ferroelectric domain walls in the crystals drastically limits their optical transparency as a result of light scattering and reflection at domain walls arising from the difference in refractive indices of the adjacent domains with different orientations, rendering high optical loss or even opacity in the visible-to-near-infrared spectrum. In the past few decades, considerable efforts have been made to eliminate the light-scattering domain walls in these ferroelectrics, but with very limited success ( 13 21 ). For example, poling a ferroelectric crystal along its polar direction can achieve a single-domain state without domain walls.…”
mentioning
confidence: 99%
“…Though this process achieved good transparency and ultrahigh piezoelectricity, the optical properties of those crystals cannot be easily modulated. Only very recently, Deng et al [31] demonstrated that domainengineered rhombohedral crystals of PMN-PT can have large piezoelectric and electro-optic effects.…”
Section: Introductionmentioning
confidence: 99%